Biosynthesis Of Poly(3-Hydroxybutyrate) By Cupriaviadus Necator Dsm 428 Utilizing Waste Date Fruits As A Carbon Source - Wahab, Siti Nur Aqilah Binti Abdul (Universiti Sains Malaysia, 2020)
Many researches have been conducted to find a replacement for conventional petroleum-derived plastics. Poly(3-hydroxybutyrate) (PHB) is biodegradable polymers produced from a renewable source have gained many interest to replace conventional plastic, as it possesses excellent chemical and physical properties, with an advantages of complete biodegradability. The limitation in producing huge amount of PHB is due to its expensive cost of carbon sources. This study focus on the production of PHB by Cupriavidus necator using low-cost carbon sources such as waste of date fruits.